Engaging political philosophy an introduction - Talisse, Robert B. (Routledge, 2016)
Engaging Political Philosophy introduces readers to the central problems of political philosophy. Presuming no prior work in the area, the book explores the fundamental philosophical questions regarding freedom, authority, justice, and democracy. More than a survey of the central figures and texts, Engaging Political Philosophy takes readers on a philosophical exploration of the core of the field, directly examining the arguments and concepts that drive the contemporary debates. Thus the fundamental issues of political philosophy are encountered first-hand, rather than through intermediary summaries of the major texts and theories. As a result, readers are introduced to political philosophy by doing philosophy. Written in a conversational style, Engaging Political Philosophy is accessible to students and general readers. Instructors can use it in the classroom as a stand-alone textbook, a complement to a standard collection of historical readings, or as a primer to be studied in preparation for contemporary readings -- Amazon.